2001
DOI: 10.1007/s11664-001-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced titanium disilicide formation for submicron technologies

Abstract: A great deal of studies on thin-film silicides have been conducted over the past 15 years due to their applications in the fabrication of complementary metal oxide semiconductor devices. 1-7 Silicides can significantly reduce the contact resistance of the gate electrode and the source/drain regions as compared to nonsilicided structures. In particular, titanium disilicide (TiSi 2 ) has been used extensively as a contact material in ultra-large-scale integration technology because of its low electrical resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Pulsed laser annealing has also been investigated and several important benefits have been demonstrated. First, due to its fast ramping rate and short anneal duration, nanosecond laser annealing (UV-NLA) has been found to enable the formation of smaller grains of C49-TiSi2 than RTA [30][31][32] , increasing the density of C54-TiSi2 nucleation sites. Chen et al 30 have also reported that the transformation temperature into C54-TiSi2 can be significantly reduced by pulsed laser annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsed laser annealing has also been investigated and several important benefits have been demonstrated. First, due to its fast ramping rate and short anneal duration, nanosecond laser annealing (UV-NLA) has been found to enable the formation of smaller grains of C49-TiSi2 than RTA [30][31][32] , increasing the density of C54-TiSi2 nucleation sites. Chen et al 30 have also reported that the transformation temperature into C54-TiSi2 can be significantly reduced by pulsed laser annealing.…”
Section: Introductionmentioning
confidence: 99%
“…investigation performed so far on leveraging UV-NLA for the formation of TiSi2 have been mainly conducted with small laser beams (diameter ~160-200 µm) with a near Gaussian shape scanning the surface with a controlled speed, resulting in a large number of pulses at the same location (typically more than 100 pulses) [30][31][32][33][34][35][36] . Such studies did not properly explore the effect of the laser energy density.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to eliminate the fine line effect that occurs during the Ti silicide transformation from C49 to C54 phase. A fine and nanogram of C49 can be achieved by using single pulsed laser annealing, in which subsequently the formation temperature of C54 TiSi 2 can be lowered [44].…”
Section: Transient Annealingmentioning
confidence: 99%